Optimizing Health Services: A Quality Study at Community Health Centers in Sukoanyar Village, Lamongan - Sanindita Qolbiyah Hariroh; Tukiman Tukiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Health is a fundamental right of every individual and a key factor in achieving social welfare. In Indonesia, health development is aimed at improving access to and quality of health services that are equitable, affordable, and of high quality. This study aims to assess the quality of outpatient services at the Turi Subdistrict Health Center, Lamongan Regency, based on the five Servqual dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. A quantitative research method was employed, with a random sample of 100 outpatients selected from an average population of 3,159 patients over the past six months. Data were collected using a structured questionnaire with a four-point Likert scale and analyzed descriptively. The research results show that the five dimensions of service quality, received positive ratings from the majority of respondents, with agreement rates ranging from 75% to 78%. Physical facilities and cleanliness support patient comfort, while services generally align with established promises and procedures. Staff are also rated as responsive and capable of providing clear information, although administrative procedures still need to be simplified. Staff competence and polite attitudes create a sense of safety and trust among patients. Staff attention to individual patient needs further enhances the positive relationship between patients and healthcare personnel. This study confirms that the quality of outpatient services at Turi Health Center is already of good quality, but continuous improvement is still needed, particularly in simplifying administrative procedures. These findings can serve as a basis for developing policies to improve the quality of healthcare services at the local level.